2020
DOI: 10.3389/fpsyg.2019.02936
|View full text |Cite
|
Sign up to set email alerts
|

“The Worst Part Was Coming Back Home and Feeling Like Crying”: Experiences of Lesbian, Gay, Bisexual and Trans Students in Portuguese Schools

Abstract: Portugal is one of the most egalitarian countries in Europe in terms of lesbian, gay, bisexual, transgender, and intersex (LGBTI) individuals' legal rights. However, regarding education Portugal still lacks specific policies, plans and interventions to protect LGBTI students. To assess the perceptions of self-identified LGBTI youth regarding their school context, a total of 663 participants (aged from 15 to 20 years old) filled in an on-line questionnaire about their school climate. One hundred and forty-six o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 69 publications
1
14
0
3
Order By: Relevance
“…None of the participants identified family as a strong source of support. This supports recent research by Gato et al (2020) who found that LGBTQ+ young people tend not to identify their families as a source of social support, despite this being a dominant theme in the general literature on resilience (Roffey, 2017). For some, relationships with family members had become impaired due to the disclosure of their sexuality or gender identities (Christopher, Mark, Elizabeth).…”
Section: Resiliencesupporting
confidence: 87%
“…None of the participants identified family as a strong source of support. This supports recent research by Gato et al (2020) who found that LGBTQ+ young people tend not to identify their families as a source of social support, despite this being a dominant theme in the general literature on resilience (Roffey, 2017). For some, relationships with family members had become impaired due to the disclosure of their sexuality or gender identities (Christopher, Mark, Elizabeth).…”
Section: Resiliencesupporting
confidence: 87%
“…According to Gato et al (2020), During recess and if I was alone it was common to be called gay (Male, 19, gay, cisgender). .…”
Section: Subtheme 12: Emerging Of An Intersectional Awarenessmentioning
confidence: 99%
“…Onde está o direito à autodeterminação de género e sexualidade nas crianças e jovens? Estando as instituições -e práticas profissionais -influenciadas por um sistema estrutural que reproduz valores cis-heteronormativos, são também elas palco de violências e fenómenos de marginalização que comprometem a igualdade no acesso à educação (Evans e Rawlings 2019; IGLYO e UNESCO 2021) e à saúde (Ceatha et al 2020;Gato et al 2020; Wilson e Cariola 2020). Por outras palavras, a cis-heteronormatividade regula a forma como a diversidade de género e sexual é ou não «acolhida» e garantida nos diferentes espaços institucionais, produzindo diferentes efeitos transversais, interseccionais e ao longo da vida.…”
Section: Impactos Do Adultocentrismo Na Regulação Da Diversidade Sexual E De Género Na Infância E Juventude -Considerações Finaisunclassified